Postoperative quality of life in patients with early-stage cervical cancer: A prospective 10-year follow-up study - Maxova, Katerina; Rehackova, Martina; Jirkovska, Michaela; Robova, Helena; Rob, Lukas; Halaska, Michael J (European journal of surgical oncology, 2025)
INTRODUCTION: The substantial improvement in early-stage cervical cancer survival rates has given rise to the significance of subsequent quality of life. This study aims to assess the quality of life in patients subjected to radical and conservative surgeries for cervical cancer. MATERIALS AND METHODS: One hundred patients diagnosed with early-stage cervical cancer (stages IA2-IIA1) undergoing surgical treatment were enrolled in our study between 2007 and 2011. Patients completed quality of life questionnaires EORTC QLQ-C30 and QLQ-CX24, distributed before the surgery, 6, 12, and 120 months after the procedure. At the final 120-month follow-up, 54 patients remained eligible for inclusion. 23 patients ("CONS group") underwent laparoscopic lymphadenectomy combined with hysterectomy or simple trachelectomy. The remaining 31 patients ("RAD group") underwent abdominal radical hysterectomy type C1. RESULTS: At the 6-month post-surgery assessment, the RAD group reported a significantly higher incidence of menopausal symptoms, decline in physical functioning and concern regarding their sexual well-being. CONS group patients reported notable exacerbation of lymphedema and neuropathy-related symptoms but only a slight decline in physical functioning. Additionally, their role functioning, emotional well-being, and social functioning significantly improved compared to their preoperative baseline. At the 120-month postoperative assessment the RAD group showed a significant decline in several parameters, including lymphedema, peripheral neuropathy, postmenopausal symptoms, fatigue, pain, and physical functioning. CONCLUSIONS: Cervical cancer treatment is invariably associated with a negative long-term impact on quality of life, RAD group demonstrated poorer outcomes than the CONS group across multiple parameters but even the CONS group exhibited long-term effects of the surgery.
Keywords: následné studie; Female; lidé středního věku; nádory děložního čípku; Quality of Life; Laparoscopy; Follow-Up Studies; průzkumy a dotazníky; lymfedém; kvalita života; staging nádorů; lymfadenektomie; prospektivní studie; Humans; dospělí; Prospective Studies; laparoskopie; hysterektomie; Postoperative Complications; Postoperative Period; lidé; Middle Aged; Trachelectomy; Surveys and Questionnaires; Neoplasm Staging; senioři; trachelektomie; Lymph Node Excision; Uterine Cervical Neoplasms; ženské pohlaví; Aged; pooperační komplikace; pooperační období; Lymphedema; Adult; Hysterectomy